Pengetahuan, Dukungan Suami dan Peran Tenaga Kesehatan Dalam Keberhasilan ASI Eksklusif Pada Ibu Yang Memiliki Bayi 0-6 Bulan: Knowledge, Husband's Support and the Role of Health Workers in the Success of Exclusive Breastfeeding for Mothers with Babies 0-6 Months - Assyuro Cahya Pertiwi Marsal, Mulia Mustika Ningsih Marsal; Baska, Dwie Yunita; Wahyuni, Elly; mariati, Mariati; Yorita, Epti (JURNAL BESUREK JIDAN, 2025)
Background: Exclusive breastfeeding in Indonesia is still lower than the specified amount. In Bengkulu Province, especially in Bengkulu City, the coverage of exclusive breastfeeding is only around 61.9% and it was found that the lowest was at the Kandang Community Health Center in Bengkulu City with a percentage of (27.0%). Objective: This research is to determine the factors that influence exclusive breastfeeding for babies 0-6 months in the Kandang Community Health Center working area, Bengkulu City in 2024. Methodology: This type of research uses a cross-sectional research method with the Accidental Sampling technique. The population in this study were all mothers who had babies 7-12 months in the Kandang Community Health Center working area, Bengkulu City in 2024, totaling 99 mothers. Data collection used the Chi-Square Test and Multivariate Logistic Regression Test. Research: The results of the study show that there is a relationship between knowledge with a P-value of 0.003, there is no relationship with husband's support with a P-value of 0.875 and there is no relationship with the role of health workers with a P-value of 0.424 in giving exclusive breastfeeding. The most dominant factor influencing exclusive breastfeeding is knowledge with a value of OR= 3.521. Conclusions and Suggestions: Suggestions to health workers, especially midwives, are expected to be able to provide information about giving exclusive breastfeeding to pregnant women or to mothers during the exclusive breastfeeding period by providing education through classes for pregnant women or through counseling when conducting posyandu.